COMPARATIVE ANALYSIS OF THE EFFECTIVENESS OF ARCHITECTURAL STYLES REST, GRAPHQL, AND GRPC FOR SCALABLE MICROSERVICE SYSTEMS - SIKORA, ROSTYSLAV; POSTOLIUK, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The microservice architectural pattern has rapidly emerged as a dominant and highly effective approach for building complex, distributed, and scalable applications in modern software engineering. By judiciously decomposing monolithic applications into a collection of small, independent, and loosely coupled services, organizations are increasingly able to achieve significant gains in agility, resilience, and maintainability. This decomposition facilitates independent development, deployment, and scaling of individual components, which is crucial for handling the dynamic demands of contemporary systems. As the adoption of microservices continues to grow and mature across various industries, the selection of appropriate communication protocols and architectural styles to govern interactions between these discrete services has become an increasingly critical and strategic decision. The chosen architectural style profoundly impacts various non-functional requirements and overall system effectiveness, including but not limited to scalability, performance, ease of development, integration complexity, and operational efficiency. This paper undertakes a comprehensive comparative analysis of three prominent and widely adopted architectural styles frequently employed in modern microservice architectures: Representational State Transfer (REST), GraphQL, and gRPC (Google Remote Procedure Call). While each of these styles inherently offers distinct advantages and disadvantages, their ultimate suitability is often highly contingent upon the specific requirements, constraints, and operational context of the target application. Our research delves deeply into the core principles, underlying technologies, and defining characteristics of each of these architectural styles, providing a robust theoretical understanding that underpins the subsequent comparative evaluation. The comparative evaluation will assess the effectiveness of these styles based on a meticulously defined set of key criteria, encompassing critical aspects of distributed system design: scalability, performance, development and integration simplicity, support for various interaction types (e.g., streaming), observability, and security. For instance, we will analyze how REST’s statelessness and caching capabilities contribute to scalability, while also examining its potential for over-fetching and under-fetching, which can impact performance. For GraphQL, we will highlight its client-driven data fetching capabilities, which precisely mitigate these issues, but also consider the increased server-side complexity and challenges in caching. In the case of gRPC, the analysis will focus on its high performance due to Protocol Buffers and HTTP/2, as well as its strengths in efficient streaming, while acknowledging potential complexities in browser integration and debugging. Ultimately, this research aims to offer nuanced insights into when each architectural style might represent the most appropriate and effective choice for building highly scalable and resilient microservice systems. By examining the theoretical foundations and practical implications, alongside real-world case studies and industry experiences, this paper seeks to provide a comprehensive and practical guide for architects and developers who are navigating the inherent complexities of modern distributed system design and striving to make informed decisions regarding inter-service communication paradigms. The structured approach of this article will first lay the theoretical groundwork for each architectural style, then establish the criteria for a comparative analysis, followed by a detailed comparison, discussion of potential case studies and real-world implementations, an exploration of existing challenges and promising future research directions, and finally, a concise concluding summary of the findings. This structured analysis will empower practitioners to select the most suitable architectural style, thereby contributing to the development of more efficient, robust, and maintainable distributed applications.